Analysis of Students’ Errors in Solving Word Problems on Probability Material for Grade VIII based on Newman’s Stages in Terms of Mathematical Ability Levels - Andini Rusdianawati; Rustanto Rahardi; Imam Rofiki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The purpose of this study is to describe the types of errors that arise when students solve probability problems by applying Newman’s stages, viewed from students’ levels of mathematical ability. This descriptive study employed a qualitative approach. The research subjects consisted of six eighth-grade students from MTs Al Huda. The subjects were selected using purposive sampling techniques. The instruments used in this study included a written test and an interview guide. The written test consisted of two items, and the interview guide was validated by experts and declared valid. Students with high mathematical ability made errors at the process skill stage. The leading cause of errors among students with high mathematical ability was poor calculation accuracy. Meanwhile, students with moderate mathematical ability made errors at the transformation and process skill stages. The primary factors causing errors among students with moderate mathematical ability were a lack of understanding of changes in the sample space in situations without replacement and insufficient understanding of fraction simplification rules. On the other hand, students with low mathematical ability experienced errors at the reading, transformation, process skill, and encoding stages. Several significant factors contributing to errors made by students in the low-ability category include: (1) errors in interpreting words or terms in the problems, (2) a lack of understanding of probability concepts, (3) insufficient understanding of fraction simplification rules, and (4) inability to conclude the solutions in accordance with the given problems.